1995
DOI: 10.1002/eji.1830251133
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of residue 116 of HLA‐B27 in determining susceptibility to ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS) is an autoimmune disorder strongly associated with HLA-B27. A direct role of B27 molecules in the disease pathogenesis has been postulated, possibly by presenting to T cells an as-yet unidentified arthritogenic peptide that triggers the autoimmune response. There are nine HLA-B27 alleles differing from each other at one or more amino acid positions. It is important, for the identification of the arthritogenic peptide, to define which alleles, and therefore which polymorphic position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
125
0
6

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(138 citation statements)
references
References 18 publications
7
125
0
6
Order By: Relevance
“…The differential association of B*2704 and B*2706 with AS in populations of Southeast Asia has been reported in 3 independent studies (17)(18)(19). The differential association between B*2705 and B*2709 and AS was established in Sardinia, the only place where B*2709 is found at a significant frequency (20,21). Both of these subtypes are in differential linkage disequilibrium with distinct MHC haplotypes in this population (22), raising the possibility that a non-B27 gene in linkage disequilibrium with B*2709 would protect against disease.…”
mentioning
confidence: 79%
“…The differential association of B*2704 and B*2706 with AS in populations of Southeast Asia has been reported in 3 independent studies (17)(18)(19). The differential association between B*2705 and B*2709 and AS was established in Sardinia, the only place where B*2709 is found at a significant frequency (20,21). Both of these subtypes are in differential linkage disequilibrium with distinct MHC haplotypes in this population (22), raising the possibility that a non-B27 gene in linkage disequilibrium with B*2709 would protect against disease.…”
mentioning
confidence: 79%
“…For example, wild-type HLA-B27 (and B27.H9F), but neither B27.A2B nor B27.E45M, tends to form HC dimers and even larger aggregates on the surface of C1R transfectants (11). D'Amato et al (12) have shown that these complexes may form during endosomal recycling and, thus, could conceivably affect phagolysosomal fusion and promote an environment that is permissive of bacterial replication. Further experiments will be required to investigate the mechanisms that lead to altered permissiveness for bacterial replication.…”
Section: Discussionmentioning
confidence: 99%
“…Misfolding is associated with the formation of aberrant disulfide-linked HC complexes in the ER, including homodimers (11). HC homodimerization also appears to occur distal to the ER and/or during HC recycling from the cell surface (11,12) in a process that is associated with loss of ␤ 2 -microglobulin and/or peptide, and it appears to be distinct from ER misfolding. Altering amino acids that comprise the B pocket, a region in the peptide-binding groove that also has a dominant influence on peptide selection (13)(14)(15), can correct misfolding.…”
mentioning
confidence: 99%
“…The increased accuracy in the description of MHC polymorphism associated with diseases is especially exemplified in the case of HLA-B27 and SA. The lower disease association of B*2703, B*2706, and B*2709 subtypes is based on epidemiological studies (6)(7)(8), even if B*2703 or B*2706 patients with B27-associated diseases have been reported occasionally (34,35). Larger population studies will be needed before final conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to assess the disease association of the B*2701 and B*2708 subtypes since these are rarely occurring. Other subtypes could be less tightly associated with SA at the population level, especially B*2703 which is the most frequent subtype in West Africa (6), B*2706 in the Thai population (7) and B*2709 in Sardinia (8). This could reflect a differential binding of peptides derived from an autoantigen and/or from environmental agents since the role of bacterial infection on SA triggering has been shown in humans (9) and in the HLA-B27 transgenic rat model (10).…”
Section: Introductionmentioning
confidence: 99%